PENGARUH EDUKASI GIZI MELALUI MEDIA INTERACTIVE BOOK TERHADAP PENGETAHUAN DAN SIKAP TENTANG MAKANAN SEHAT PADA ANAK UMUR 9-12 TAHUN - Safira Rizki Amalia; Vitria Melani; Laras Sitoayu; Yulia Wahyuni (UHAMKA PRESS, 2023)
School-age children often do not pay attention to the quality and quantity of their food consumption. Therefore, nutrition education about healthy food is needed to increase their knowledge and attitudes in choosing healthy food to support their growth and development. This study aimed to analyze the effect of nutrition education through the media